2018
DOI: 10.1021/acs.inorgchem.8b01923
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide Tetranuclear Cage and Mononuclear Cocrystalline Nitronyl Nitroxide Complex with Single-Molecule-Magnet Behavior

Abstract: The first tetranuclear metallacage and mononuclear cocrystalline DyIII-radical complex was synthesized and characterized. The metallacage in [Dy4(hfac)8(IMPhThio)2(OH)4]­[Dy­(hfac)3(NITPhThio)2] consists of Dy­(hfac)2 + groups bridged by OH– and the IMPhThio radical. Field-induced single-molecule-magnet behavior was observed in the nitronyl nitroxide radical-bridged polynuclear complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 75 publications
2
6
0
Order By: Relevance
“…The plot of ln τ versus T –1 exhibits linear correlation, which indicates that the magnetic spin was reversed by a thermally activated Orbach mechanism process (Figure b) . With the help of the Arrhenius equation [τ = τ 0 exp­(Δ eff / k B T )], an effective energy gap of 14 K and a preexponential τ 0 of 3.1 × 10 –7 s were obtained, which are consistent with those of the reported SMMs. ,,, , In addition, on the basis of the frequency dependence of the ac susceptibility data, Cole–Cole plots (χ″ versus χ′) with nearly semicircular shapes were obtained (Figure S11). With the help of a generalized Debye model, the distribution coefficient α was fitted, and the value was in the range of 0.39–0.28 (between 2 and 3.2 K), which indicates a narrow distribution of the magnetization relaxation time.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…The plot of ln τ versus T –1 exhibits linear correlation, which indicates that the magnetic spin was reversed by a thermally activated Orbach mechanism process (Figure b) . With the help of the Arrhenius equation [τ = τ 0 exp­(Δ eff / k B T )], an effective energy gap of 14 K and a preexponential τ 0 of 3.1 × 10 –7 s were obtained, which are consistent with those of the reported SMMs. ,,, , In addition, on the basis of the frequency dependence of the ac susceptibility data, Cole–Cole plots (χ″ versus χ′) with nearly semicircular shapes were obtained (Figure S11). With the help of a generalized Debye model, the distribution coefficient α was fitted, and the value was in the range of 0.39–0.28 (between 2 and 3.2 K), which indicates a narrow distribution of the magnetization relaxation time.…”
supporting
confidence: 85%
“…The static direct-current (dc) magnetic susceptibility for complex 1 is studied and shown in Figure S5. The observed room temperature χ M T product is 36.06 cm 3 ·K·mol –1 , which is very close to the theoretical value of 36.14 cm 3 ·K·mol –1 for three isolated Tb III ions and two organic radicals. Following a decrease of the temperature, the value of χ M T diminished slowly at first and then accelerated appropriately until it reached the minimum value of 32.88 cm 3 ·K·mol –1 at 24 K. Following a further decrease in the temperature, it showed a fast upward trend up to 36.74 cm 3 ·K·mol –1 at 2 K. In the high-temperature range, the decrease of the χ M T value upon lowering of the temperature may be attributed to depopulation of the Tb III Stark sublevels, while in the low-temperature region, the increase of the temperature dependence of the magnetic susceptibility reveals ferromagnetic interactions between the spin carriers. In addition, the nonsuperposition properties on the M versus H / T curves at 2, 3, and 5 K temperatures show the existence of magnetic anisotropy and/or low-lying excited states in the Tb 3 system (Figure S5b).…”
supporting
confidence: 78%
“…In 2018, K. R. Dunbar et al, reported the first metallacycle [Dy 3 (hfac) 6 (bptz −• ) 3 ](bptz = 3,6-bis(2-pyridyl)-1,2,4,5-tetrazine; hfac = hexafluoroacetylacetonate) exhibiting temperature-dependent out-of-phase (χ") signals in the high-frequency range [15]. Noticeable, most of radical-Ln based molecular nanomagnets are constructed using mono-radicals [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], and the employments of biradicals are less common [23][24][25][26][27][28]. Nitronyl nitroxide biradical-Ln approach, one hand, can result in interesting spin topology in which the unique magnetic behavior could be observed.…”
Section: Introductionmentioning
confidence: 99%
“…Although the lanthanide based cocrystals are sparse, a handful contemporary reports on ligand‐coordinated along with uncoordinated anion‐bonded lanthanides as well as additives ligands with lanthanide coordinated complexes have been recognized , . Most recently, Liu and co‐workers has reported molecular magnet behavior of cocrystal containing a tetranuclear metallocage and mononuclear Dy III ‐radical complex . As a matter of fact, there has been a ever‐present interest in the field of lanthanide coordination chemistry due to their promising applications for the development of catalysts and photoluminescent and molecular magnetic materials.…”
Section: Introductionmentioning
confidence: 99%